Proposed Productivity Improvement of 1800 Press Machine Using Overall Equipments Effectiveness - Murwan Widyantoro; Yuri Delano Montororing; Paduloh Paduloh; Solihin Solihin; Murhaban Murhaban (universitas teuku umar, 2021)
Increased productivity is an effort to increase production capacity by increasing the productivity of each factor of production. PT XYZ is a company that uses sophisticated machines and facilities to produce aluminium profiles that create various needs in the form of building goods or furniture products in the form of doors, windows, partitions, frames, rolling doors, etc. One of the machines used is the 1800 press machine. This study aims to increase productivity with Overall Equipment Effectiveness (OEE) to make improvements. Based on the calculation of the Overall Equipment Effectiveness (OEE) of the 1800 press machine during January - December, the final value was 52%, this value indicates that the effectiveness of the 1800 press machine has not reached the ideal deal of 85% so that some improvements are needed. The company experiences the three most considerable losses: Breakdown Losses, Setup and Adjustment Losses, and Reduce Speed Losses, so repairs must be made to these three losses so that the 1800 press machine can achieve its best performance. Keywords— Overall Equipments Effectiveness (OEE), Six Big Losses, 1800 press machine